HGG-08. ATRX LOSS IN PEDIATRIC GBM RESULTS IN EPIGENETIC DYSREGULATION OF G2/M CHECKPOINT MAINTENANCE AND SENSITIVITY TO ATM INHIBITION. (23rd April 2019) - Mullan, Brendan; Qin, Tingting; Siada, Ruby; Danussi, Carla; Brosnan-Cashman, Jacqueline; Pratt, Drew; Garcia, Taylor; Yadav, Viveka Nand; Zhao, Xinyi; Morgan, Meredith; Venneti, Sriram; Meeker, Alan; et al.
Abstract: ATRX is a histone chaperone protein recurrently mutated in pediatric GBM. We previously confirmed its role in tumor progression and mutational burden in glioma. However, the mechanism which mediates the proliferative advantage of ATRX loss in pediatric GBM remains unexplained. Recent data revealed a distinct pattern of DNA binding sites of the ATRX protein using ChIP-seq in mouse neuronal precursor cells (mNPCs). Using the ATRX peaks identified in p53 -/- mNPCs, we confirmed that ATRX binding sites were significantly enriched in gene promoters (p<0.0001) and CpG islands (p<0.0001) compared with random regions. Gene set enrichment (GSE) analysis identified that cell cycle and regulation of cell cycle were among the most significantly enriched gene sets (p=2.52e-16 and 1.61e-9, respectively). In line with this, the master cell cycle regulator CDKN1A was significantly down-regulated (p=0.0024) in human pediatric high-grade gliomas with ATRX mutation (PedsCbioPortal, n=247). We found that ATRX loss resulted in dysfunction of G2/M checkpoint maintenance: (1) ATRX-deficient pediatric GBM cells exhibited a seven-fold increase in mitotic index at 16 hours after sub-lethal radiation, and (2) murine GBM cells with ATRX knockdown demonstrated impaired pChk1 signaling on western blot at multiple time points after radiation compared to controls (p=0.0187). Notably the ATM signaling (pChk2) remained intact in those cells, suggesting a potential therapeutic target. ATRX-deficient mouse cells were uniquely sensitive to ATM inhibitors at 1 uM alongside 8 Gy radiation compared to controls with intact ATRX (AZD0156: p=0.0027 and AZD01390: p=0.0436). Using an ATM-luciferase reporter assay, AZD0156 demonstrated stronger ATM inhibition when compared to AZD1390. Mice intra-cranially implanted with ATRX-deficient GBM cells showed improved survival (n=10, p=0.0018) when treated with AZD0156 combined with radiation. Our findings suggest that ATRX loss in glioma results in unique sensitivity to ATM inhibition via epigenetic dysregulation of G2/M checkpoint maintenance.